High-yield biogenic fabrication and phytochemical screening of silver nanomaterials (AgNMs) from Kaempferia parviflora rhizome extract - Azman, Alya Khaizura; Aidiel, Mohammad; Van Oosterhout, Deborah Anna; Abdul Mutalib, Maisarah (Life Sciences, Medicine and Biomedicine, 2024)
Nanotechnology is one of the promising scientific advancements that has captured widespread interest across various industries, notably in medicine. The utilization of plants for the synthesis of silver nanomaterials (AgNMs) has emerged as a promising and eco-friendly approach, offering cost-effective solutions for potential biomedical applications. The study aims to optimize the efficiency of biogenic AgNMs fabrication by employing Kaempferia parviflora aqueous extraction (KP-AE) as both a reducing and encapsulating agent, thus optimizing the yield of AgNMs. Phytochemical screening was conducted to identify the phytochemical compounds present in KP-AE. Various parameters were optimized, including pH, temperature, and the ratio of KP extract to AgNO3, over different incubation periods. The synthesized AgNMs were analyzed spectroscopically and microscopically using UV-Vis and SEM techniques. At varying concentrations of KP and AgNO3, the KP-AE AgNMs were successfully biogenic fabricated, but the yields varied. As the concentrations of AgNO3 increased, a greater yield of KP-AE AgNMs was achieved. Phytochemical screening KP-AE demonstrated the presence of potential phytochemicals such as alkaloids, saponins, tannins, flavonoids, terpenoids, glycosides, and oils that assisted in the biogenic fabrication of AgNMs. This study established an efficient, affordable, and ecologically sustainable approach for fabricating stable AgNMs using KP-AE AgNMs. Synergistically, reducing and capping potential has been achieved by combining the plant extract in plant-mediated biogenic fabrication, producing stabilized NMs compared to those produced individually. The AgNMs derived from KP-AE exhibit robust antioxidant properties, showcasing promise for further exploration in pharmaceutical applications. Additional research is needed to investigate the biological potential and pharmacological properties of the biogenic fabricated KP-AE AgNMs.